DESIGN OF A PROMOTION MIX STRATEGY ON SEVEN FLORIST - Renza Fahlevi; Anthony Anthony (Universitas Internasional Batam, 2022)
With so many competitors in this business, a strategy is needed to maximize sales from this business. The promotion mix strategy can be a way to solve this problem. The promotion mix strategy used in this activity is advertising, sales promotion, and direct marketing. In carrying out this activity carried out by interviews and observations. The resulting strategies are advertising, sales promotion, and direct marketing. This strategy resulted in product catalogs, advertisements on social media, stamp cards, and letters of cooperation agreements with large companies. The result of the implementation of this activity is that the strategy can be applied in this business and has been able to increase sales. The recommendations for this activity are to adjust the location of the business and also what is needed by the business owners.